Fungicides, biocides, and preservatives for industrial and agricultural applications - Flick, Ernest W. (Noyes Publications, 1987)
This book describes approximately 350 fungicides, biocides, and preservatives, which are currently available for industrial and agricultural usage. It is applicable to industrial, agricultural, technical, and managerial personnel involved in the specification and use of these products. It has been produced from information received from numerous industrial companies and other organizations.